CAUSES OF MIGRATION AND WORKING CONDITIONS ABROAD AMONG PHYIOTHERAPISTS - Mária VIZSY; Róbert PÓNUSZ; Monika SÉLLEYNÉ GYURÓ; Luca Fanni KAJOS; Péter TARDI; István ÁGOSTON; Rita JUHÁSZ; Bálint SZŐTS; Bálint MOLICS (Cluj University Press, 2021)
Introduction: The migration of health professionals severely affects the current number of physicians and professionals in a country. Aim: The aim of our work was to investigate the reasons for the departure of physiotherapists already working abroad, to learn the working conditions abroad, and to explore the conditions for returning home. Method: Our data were obtained by a self-edited, online questionnaire survey. The number of items in our sample was 112 (N = 112) physiotherapists working abroad. Our research was conducted between November 2018 and February 2019. Results: Results of the most influential factors of migration were as follows: 62.5% (70 people) had a lack of financial reward, 55.4% (62 people) had a sense of uncertainty about the future, 49.1% (55 people) did not trust the Hungarian health care organization. The monthly salary of professionals working abroad varied between 1001-2000 Euros in 38.4% (43 people), between 2001 and 3000 in 38.4% (43 people) and was over 3000 Euros in 23.2% (26 people). 76.8% (86 people) didn't take a second job because they didn't need it. Factors influencing return were the following: 1) in 69.6% (78 people) "more favorite financial conditions", 2) in 51.8% (58 people) "better working conditions", 3) in 42.9% (48 people) "a better organized health care system. Conclusion: Physiotherapists working abroad have left mainly due to a better quality of life, a more predictable vision and more favorite financial conditions, and a change in these conditions would encourage them to return home the most.